COVID-19 lockdown impact on lifestyle habits of Italian adults - Odone, Anna; Lugo, Alessandra; Amerio, Andrea; Borroni, Elisa; Bosetti, Cristina; Carreras, Giulia; Cavalieri d'Oro, Luca; Colombo, Paolo; Fanucchi, Tiziana; Ghislandi, Simone; Gorini, Giuseppe; Iacoviello, Licia; et al. (Acta Biomedica Atenei Parmensis, 2020)
In March 2020, when the Government imposed nation-wide lockdown measures to contrast the COVID-19 outbreak, the life of Italians suddenly changed. In order to evaluate the impact of lockdown on lifestyle habits and behavioral risk factors of the general adult population in Italy, we set up the Lost in Italy (LOckdown and lifeSTyles IN ITALY) project. Within this project, the online panel of Doxa was used to conduct a web-based cross-sectional study during the first phase of the lockdown, on a large representative sample of adults aged 18-74 years (N=6003). The self-administered questionnaire included information on lifestyle habits and perceived physical and mental health, through the use of validated scales. As we are working within the Lost in Italy project, we got two additional grants to further research on the medium-term impact of lockdown, a topic of great interest and with anticipated large socio-economic and public health implications. In details: we obtained by the AXA Research Fund support to evaluate the impact of COVID-19 lockdown on physical, mental, and social wellbeing of elderly and fragile populations in the Lombardy region, the area most heavily hit by the pandemic in the country. Moreover, as a fruitful integration, we obtained support by the Directorate General for Welfare of the region to assess health services delivery and access to healthcare in the same study population, combining an analysis of administrative databases with an economic analysis. We are confident that the solid background of our partners, the multi-disciplinary competencies they bring, together with appropriate funding and access to rich data sources will allow us to fulfill our research objectives.